A questão do poder: a visão de Michel Foucault e uma análise aplicada a escola - Ramos, Cristina Maria Cordeiro (1986)
This paper aims at presenting Michel Foucault's theory on the institution and existence of disciplinary society. It also aims to show, based on Foucault's viewpoint, an analysis on the modus operandi of two 1st degree public schools from some documents. This analysis intends to make explicit the mechanisms and instruments of that discipline in the relationships maintained among members of the school, emphasizing the role of the teacher. Among these lines we make an attempt to describe Foucault's theory on disciplinary society by using his studies on patterns he developed prior to such society so as to better understand it. Therefore, such goals were determined by the need of ascertaining the viability of an analysis on the complex generating net of power relations. It was also possible to ascertain the existence of a commitment involving all the members of school concerning the production of knowledge and facts made necessary for the maintenance of the established order. Such a commitment is felt in the school practice due to the use of procedures intended at the scope and continuity of power effects brought about by those relations. The attendance to control mechanisms that support the school discipline normalizing function can be verified in the granting of functional roles to cach professional including the teacher himself. It must also be stressed the constraints imposed by the analysis scope here used, permitting one the foresce the advantages for applying this study on a more comprehensive research scope with a view to verifying the level of generality of the statements made herein, from this particular study.